EFFECT OF ASPIRIN ON RAT LIVER CLASS- GLUTATHIONE S-TRANSFERASE ACTIVITY - Enade Pradana Istyastono; Sudibyo Martono; Supardjan AM (Indonesian Journal of Pharmacy, 2002)
Inflammation is the response of living tissues caused by injury. It involves a complex battery of enzyme activation, mediator release, extravasation of fluid, cell migration, tissue breakdown and repair. Inflammation mediator is synthesized in the body by several steps and catalyzed by several enzymes, such as cyclooxygenase and class- glutathione S-transferases (GSTs) in the cyclooxygenase arachidonic acid cascade. Aspirin, which has been reported as an inhibitor to inflammation mediator synthesis in the cyclooxygenase arachidonic acid cascade, is a non-steroid anti-inflammatory agent. The aim of this research is to study the effect of aspirin on rat liver class- GST activity in vitro. GSTs were isolated from the rat liver cytosolic fraction by centrifugation according to Lundgren. Protein concentration in the cytosol was determined spectrophotometrically using bovine serum albumin as a standard. The GST activity was determined using conjugation reaction rate between glutathione (GSH) and 1,2-dichloro-4-nitrobenzene (DCNB), followed by determining IC50 of aspirin. Then, a study was done to determine the ability of aspirin in inhibition of the rat liver class- GST activity in vitro. It can be concluded that aspirin has no inhibitory effect on rat liver class- GST activity.Key word: Aspirin, anti-inflammatory, glutathione S-transferase.